A sociology of immigration : (re)making multifaceted America - Morawska, Ewa T. (Palgrave Macmillan, 2009)
"This study focuses on the interactive framework in which immigrants, responding to circumstances not of their choosing, nonetheless make history. Though the book is shaped by an underlying theoretical framework, the key theoretical issues are explored through a comparison of eight different groups, providing rich, empirical, grounded material. As the groups range widely in origins and immigrant experiences, they shed light on one of the salient aspects of the contemporary immigrant phenomenon, namely its diversity. The concluding chapter offers a thoughtful review of the main agendas of immigration research in different regions of the world followed by the author's suggestions regarding better-informed cross-national/regional studies in this field."--Book cover.